DESAIN SISTEM INFORMASI KEDISIPLINAN SISWA DI SEKOLAH MENEGAH KEJURUAN NEGERI 1 BUKITTINGGI - Sarwo Derta (AMIK Mitra Gama, 2020)
Discipline is an indicator of personal success. To adapt it needs practice and instill self-awareness starting from an early age. School is a place for self-discipline education especially for students. The role of technology is also very necessary in controlling and supervising students discipline at school. SMKN 1 Bukittinggi has a system to discipline students, but it is still done in the conventional way such as recording, giving sanctions to students who violate the discipline. To help and facilitate the school, needed a computerized system that can record, recap and given sanctions automatically. This research was conducted with the ADDIE (Analyze-Design-Develop-Implement-Evaluate) version of the Research and Development method while for the system development used the Waterfall SDLC model. Information system products tested obtained a validity test value with an average value of 87.75 which is very valid, the practicality test researchers got an average value of 92 which is very practical, and the effectiveness test researchers get an average value of 93.34 which is very effective.